Analisis Keselamatan dan Kesehatan Kerja Menggunakan Metode Hirarc dan Heart (Studi Kasus : PT. Paku Jaya) - Firmansyah, Muhammad Aldy; Ismiyah, Elly (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Occupational Safety and Health is one of the most important elements that must be applied in the working stages. The implementation of K3 in the workplace can create a safe, comfortable, and efficient workplace. PT Paku Jaya as one of the companies engaged in the construction sector is always committed to implementing K3 in the work area. One of the jobs that are often done by PT Paku Jaya is Cleaning Scrubbing. During the work process there are violations in the implementation of K3 in the work area. This can cause accidents in the work area. The methods used to conduct occupational safety and health analysis in this study are HIRARC and HEART. Based on the results of the study using HIRARC method, 9 types of hazards were found. Based on the analysis using HEART method, the largest HEP value is 0.192, which is opening the Blind Sprayer line. Risk control can be carried out in accordance with the hierarchy of hazard control that can be applied to Cleaning Scrubber work, namely Engineering, Administrative Control, and PPE.